2017
DOI: 10.3390/molecules22122096
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activity of LCB 01-0699, a Prodrug of LCB 01-0648, against Staphylococcus aureus

Abstract: LCB01-0648 is a novel oxazolidinone compound that shows potent antibacterial activities against most Gram-positive cocci, including the multi-drug resistant Staphylococcus aureus. In this study, in vivo activity of LCB01-0699, a LCB01-0648 prodrug, against S. aureus was evaluated in comparison with that of Linezolid. The results of the systemic infection study demonstrated that LCB01-0699 was more potent than Linezolid against methicillin-susceptible and -resistant S. aureus strains. The in vivo efficacy of LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…LegoChem Biosciences, Inc. (Daejeon, South Korea) has developed several oxazolidinone derivatives as antibacterial agents in the last decade. 32–35 For example, compound 13 (LCB01-0062) (Fig. 2) showed in vitro activity against clinical isolates of Gram-positive bacteria compared to several antibacterial drugs, including linezolid, erythromycin, ciprofloxacin, and vancomycin.…”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…LegoChem Biosciences, Inc. (Daejeon, South Korea) has developed several oxazolidinone derivatives as antibacterial agents in the last decade. 32–35 For example, compound 13 (LCB01-0062) (Fig. 2) showed in vitro activity against clinical isolates of Gram-positive bacteria compared to several antibacterial drugs, including linezolid, erythromycin, ciprofloxacin, and vancomycin.…”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%
“…2 ). 32 Pharmacokinetic (PK) studies in a rat model demonstrated that most of compound 15 was converted to the parent compound 14. The AUC last (area under the concentration–time curve from time zero to the last sampling time) of compound 15 was found to be 5.08 mg h L −1 whilst the AUC last of compound 14 was 85.0 mg h L −1 .…”
Section: Oxazolidinones As Antibacterial Agentsmentioning
confidence: 99%
See 1 more Smart Citation